Anxiety, Reinforcement Sensitivity and Social Context in Accepting the Experience of Pain Among Rheumatoid Arthritis Patients - Pinel, Luis; Perez-Nieto, Miguel A.; Redondo, Marta; Rodríguez-Rodríguez, Luis; León, Leticia (Frontiers in Psychiatry, 2020)
Background Acceptance has become one of the most widely studied processes regarding chronic pain because of its ability to influence patients’ adaptation and coping responses. Leading researchers have found relationships between variables such as anxiety, reinforcement sensitivity, and the responses of the patients’ environment to their behaviour and acceptance. In contrast, few studies have been found that investigate the variables that predict the acceptance of pain. This study has set out to explore the relationships between pain-related anxiety, sensitivity to contingencies, and the punishment responses of significant people toward pain behaviours regarding pain acceptance. Methods With a view to fulfilling this purpose, a cohort of 62 patients with rheumatoid arthritis was chosen, and the subjects were assessed through the following self-report measures: Chronic Pain Acceptance Questionnaire, CPAQ; Pain Anxiety Symptoms Scale, PASS-20; The Sensitivity to Punishment and Sensitivity to Reward Questionnaire, SPSRQ, and The West Haven-Yale Multidimensional Pain Inventory, WHYMPI. The study’s initial objectives were achieved by means of a stepwise multiple linear regression analysis Results The linear regression analyses revealed a negative and significant correlation between anxiety, reinforcement sensitivity, and the significant persons’ responses to pain behaviours and pain acceptance. Conclusion The results suggest that the identification of these variables might be important for addressing these patients’ pain. Finally, the discussion focuses on our findings’ implications as regards their use in clinical practice.